2019
DOI: 10.7554/elife.45426
|View full text |Cite
|
Sign up to set email alerts
|

Replication Study: Wnt activity defines colon cancer stem cells and is regulated by the microenvironment

Abstract: As part of the Reproducibility Project: Cancer Biology we published a Registered Report (Evans et al., 2015), that described how we intended to replicate selected experiments from the paper ‘Wnt activity defines colon cancer stem cells and is regulated by the microenvironment’ (Vermeulen et al., 2010). Here, we report the results. Using three independent primary spheroidal colon cancer cultures that expressed a Wnt reporter construct we observed high Wnt activity was associated with the cell surface markers CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Interestingly, CAFs critically contribute to the cellular heterogeneity of CRC and to the acquision of the aggressive cancer stem cell phenotype ( Vermeulen et al, 2010 ; Essex et al, 2019 ). In addition, we found that intestinal fibroblast-derived EVs carry amphiregulin (AREG), a member of the EGF ligand family, and EVs have a central role in shaping the intestinal stem cell niche ( Oszvald et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CAFs critically contribute to the cellular heterogeneity of CRC and to the acquision of the aggressive cancer stem cell phenotype ( Vermeulen et al, 2010 ; Essex et al, 2019 ). In addition, we found that intestinal fibroblast-derived EVs carry amphiregulin (AREG), a member of the EGF ligand family, and EVs have a central role in shaping the intestinal stem cell niche ( Oszvald et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This research had a great impact on the study of CSC and recently, Essex and collaborators replicated these studies and obtained similar results. They found that TME regulates the activation of the Wnt signaling pathway, increases CCSC characteristics and enhances tumor-initiating potential[ 54 ]. Regarding this, it is known that several Wnt ligands are secreted mostly by CAFs[ 53 - 56 ].…”
Section: Influence Of the Tme On Ccsc Featuresmentioning
confidence: 99%
“…Vermeulen and colleagues showed that CAF-derived hepatocyte growth factor (HGF) activates Wnt/β-catenin signaling and subsequently the clonogenicity in cancer stem cells (CSCs) isolated from CRC patients that were transiently transfected with TCF/LEF luciferase reporter vector. Moreover, HGF restored the CSC phenotype in more differentiated tumor cells both in vitro and in vivo [ 52 ]. Essex and collaborators recently replicated these studies, emphasizing the relevance of this pathway and the interaction of tumor cells with their stroma, and in the promotion and development of CRC[ 53 ].…”
Section: Tme Factors and Conditions That Modulate The Wnt/β-catenin P...mentioning
confidence: 99%
“…Activation of the c-MET pathway through HGF signaling is related to drug resistance in many types of tumors[ 111 ]. Several works have already shown that HGF is associated with both Met and β-catenin pathways[ 52 , 54 ]. Studies published by Woo and collaborators showed that this factor is related to resistance to CPT-11 in CRC cells[ 112 ].…”
Section: Role Of β-Catenin and The Tme In The Chemoresistance Of Crcmentioning
confidence: 99%